Vain sä tiedät - Linko, Jenni (Finland, 2003)
A story of 15-year-old Pia's search for sexual identity. The documentary is built around the letters of Pia and her pen pal girlfriend Päivi. Pia begins to fear exposing her feelings because of Päivi's strong religious faith, Päivi finds it hard to accept the new situation. Still they do not want to give up the friendship. Three years later, the girls spend a day together going through the old letters, in which intense feelings unfold. Finally they come to terms with the fact that the most important thing is to be honest to yourself.
Duration: 00:24:00
Keywords: Documentary films